2003
DOI: 10.1007/s00449-002-0315-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pb2+ biosorption from aqueous solution by Rhodotorula glutinis

Abstract: The yeast Rhodotorula glutinis was examined for its ability to remove Pb 2+ from aqueous solution. Within 10 min of contact, Pb 2+ sorption reached nearly 80% of the total Pb 2+ sorption. The optimum initial pH value for removal of Pb 2+ was 4.5-5.0. The percentage sorption increased steeply with the biomass concentration up to 2 g/l and thereafter remained more or less constant. Temperature in the range 15-45°C did not show any significant difference in Pb 2+ sorption by R. glutinis. The light metal ions such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 45 publications
3
37
1
Order By: Relevance
“…Therefore the R. mucilaginosa may become a potential biosorbent in removing heavy metals from polluted water. The effectiveness of biomass concentration in percentage sorption of the metals was also observed to Rhodotorula glutinis [24]. In this study copper biosorption was maximum around pH 5.0, for the two types of biomass ( Figure 1B, p,0.0001 in both cases), would be expected to interact more strongly with negatively charged binding sites on the biosorbent.…”
Section: Effects Of the Physico-chemical Factors On Biosorptionsupporting
confidence: 64%
See 1 more Smart Citation
“…Therefore the R. mucilaginosa may become a potential biosorbent in removing heavy metals from polluted water. The effectiveness of biomass concentration in percentage sorption of the metals was also observed to Rhodotorula glutinis [24]. In this study copper biosorption was maximum around pH 5.0, for the two types of biomass ( Figure 1B, p,0.0001 in both cases), would be expected to interact more strongly with negatively charged binding sites on the biosorbent.…”
Section: Effects Of the Physico-chemical Factors On Biosorptionsupporting
confidence: 64%
“…The sensitivity towards at copper of the R. mucilaginosa when subjected to minimum inhibitory concentration at different metal concentrations (50-3000 mg L through their high cysteine content and adsorption of heavy metal cations by the cellular walls [21][22].…”
Section: Resultsmentioning
confidence: 99%
“…Urrutia and Beveridge [17,18] Furthermore, it is known that the yeast Rhodotorula glutinis produces an extracellular polysaccharide composed of neutral sugars (85%) and uronic acid (15%). Uronic acids confer a net negative charge to the polymer and play an important role in the binding of metal cations [21]. Therefore, it can be supposed that the negatively charged carboxylic groups in the yeast cell wall prevent the permeation of As(V) and Cr(VI) anions into the cell while the neutralization of the carboxylic groups by methylation allows the permeation of As(V) and Cr(VI) anions into the cell.…”
Section: Proton Binding Sites Of Meyementioning
confidence: 99%
“…were resistant to heavy metal toxicity and have shown to play a role in processes of mineral cycling (26,32,33). Cho et al reported that R. glutinis and R. aurantiaca showed the high capacity of biosorption for lead (23,24). Rhodotorula sp.…”
Section: Microbial Biosorbentsmentioning
confidence: 98%